Prevalence of Intradialytic Hypertension in Patients with End-Stage Renal Disease on Maintenance Hemodialysis : Prevalence of Intradialytic Hypertension in Patients - Tariq, Maimoona; Anwar, Shahid; Usman, Hafiz Tahir; Yaqub, Salman; Ahmad, Sajjad (Pakistan Journal of Health Sciences, 2025)
Intradialytic hypertension (IDH) is emerging as a relevant and recurrent problem in end-stage renal disease patients. This can result in escalated morbidity and even fatality in the event of this not being diagnosed promptly. Objectives: To determine the prevalence of intradialytic hypertension in end-stage renal disease (ESRD) patients on maintenance hemodialysis. Methods: This descriptive cross-sectional study included adult patients with end-stage renal disease (ESRD) on maintenance hemodialysis. Data on demographic and co-morbid conditions were noted. Six dialysis sessions were observed for each patient. Presence of >10 mmHg increases in systolic blood pressure between before and after the start of four out of six dialysis sessions was used to label IDH. Descriptive analysis was run, and the factors associated with IDH were compared through a chi-square test at 5% significance level. Results: The participants had a mean age of 48.03 ± 13.2 years, with females comprising 52.8% (n=76) of the total 144 patients. Hypertension emerged as the most frequent comorbidity, affecting 77.8% (n=112), while intradialytic hypertension (IDH) was identified in 19.4% (n=28) of cases. IDH showed a significant association with diabetes (30.9% vs. 12.4%, p=0.006) and was exclusively present in hypertensive patients (p=0.001). Conclusion: IDH is a relatively common occurrence and warrants careful monitoring, particularly among individuals with hypertension and diabetes mellitus.